Mesenchymal stem cells derived exosomes: a new era in cardiac regeneration - Hossein Rayat Pisheh; Mahsa Sani (Stem Cell Research & Therapy)
Abstract Despite significant strides in medical treatments and surgical procedures for cardiovascular diseases, these conditions continue to be a major global health concern. The persistent need for innovative therapeutic approaches to mend damaged heart tissue highlights the complexity and urgency of this medical challenge. In recent years, stem cells have emerged as a promising tool for tissue regeneration, but challenges such as graft rejection and tumor formation have limited their clinical application. Exosomes, extracellular vesicles containing a diverse array of biomolecules, have garnered significant attention for their potential in regenerative medicine. The cardioprotective and reparative properties of mesenchymal stem cell-derived exosomes hold promise for the treatment of heart diseases. These exosomes can modulate various cellular processes, including angiogenesis, apoptosis, and inflammation, thereby enhancing cardiac function. Despite the growing interest, there remains a lack of comprehensive reviews synthesizing the molecular mechanisms, preclinical, and clinical evidence related to the specific role of MSC-derived exosomes in cardiac therapies. This review aims to fill that gap by exploring the potential of MSC-derived exosomes as a therapeutic strategy for cardiac diseases. This review explores the potential of mesenchymal stem cell-derived exosomes as a therapeutic strategy for cardiac diseases. We discuss the molecular mechanisms underlying their cardioprotective effects, summarize preclinical and clinical studies investigating their efficacy, and address the challenges and future perspectives of exosome-based therapies. The collective evidence suggests that MSC-derived exosomes hold promise as a novel and effective therapeutic approach for cardiac diseases. Graphical abstract